Targeting biofilms and persisters of ESKAPE pathogens with P14KanS, a kanamycin peptide conjugate - Mohamed, Mohamed F.; Brezden, Anna; Mohammad, Haroon; Chmielewski, Jean; Seleem, Mohamed N. (Biochimica et biophysica acta. General subjects, 2017)
The worldwide emergence of antibiotic resistance represents a serious medical threat. The ability of these resistant pathogens to form biofilms that are highly tolerant to antibiotics further aggravates the situation and leads to recurring infections. Thus, new therapeutic approaches that adopt novel mechanisms of action are urgently needed. To address this significant problem, we conjugated the antibiotic kanamycin with a novel antimicrobial peptide (P14LRR) to develop a kanamycin peptide conjugate (P14KanS). Antibacterial activities were evaluated in vitro and in vivo using a Caenorhabditis elegans model. Additionally, the mechanism of action, antibiofilm activity and anti-inflammatory effect of P14KanS were investigated. P14KanS exhibited potent antimicrobial activity against ESKAPE pathogens. P14KanS demonstrated a ≥128-fold improvement in MIC relative to kanamycin against kanamycin-resistant strains. Mechanistic studies confirmed that P14KanS exerts its antibacterial effect by selectively disrupting the bacterial cell membrane. Unlike many antibiotics, P14KanS demonstrated rapid bactericidal activity against stationary phases of both Gram-positive and Gram-negative pathogens. Moreover, P14KanS was superior in disrupting adherent bacterial biofilms and in killing intracellular pathogens as compared to conventional antibiotics. Furthermore, P14KanS demonstrated potent anti-inflammatory activity via the suppression of LPS-induced proinflammatory cytokines. Finally, P14KanS protected C. elegans from lethal infections of both Gram-positive and Gram-negative pathogens. The potent in vitro and in vivo activity of P14KanS warrants further investigation as a potential therapeutic agent for bacterial infections. This study demonstrates that equipping kanamycin with an antimicrobial peptide is a promising method to tackle bacterial biofilms and address bacterial resistance to aminoglycosides. •Kanamycin peptide conjugate (P14KanS) exhibited potent activity against ESKAPE pathogens.•P14KanS exerts its antibacterial effect by selectively disrupting the bacterial cell membrane.•P14KanS was superior in disrupting bacterial biofilms as compared to conventional antibiotics.•P14KanS demonstrated potent anti-inflammatory activity•P14KanS protected C. elegans from lethal bacterial infections